Buddhism and monotheism - Harvey, Peter 1951- (Cambridge University Press, 2019)
Buddhism is a religion lacking the idea of a unique creator God. It is a kind of trans-polytheism that accepts many long-lived gods, but sees ultimate reality, Nirvana, as beyond these. It does, though, see Dhamma/Dharma as a Basic Pattern encompassing everything, with karma as a law-like principle ensuring that good and bad actions have appropriate natural results. This Element explores these ideas, along with overlaps in Buddhist and monotheist ideas and practices, the development of more theist-like ideas in Mahāyāna Buddhism, Buddhist critiques of the idea of a creator God, and some contemporary Buddhist views and appreciations of monotheisms
Title from publisher's bibliographic system (viewed on 30 Jul 2019)
Keywords: Buddhism; Monotheism; Gottesvorstellung; Monotheismus; Gott; Buddhismus